Pengelolaan Keuangan: Mengatur Skala Prioritas untuk Hidup Lebih Tenang dan Bahagia - Florencia Irena Lawita; Dading Damas Ario Wicaksono; Teguh Yanto; Rosalyn Orlanda; Isha Devi Anjani (LPMP Imperium, 2025)
The Community Service Program conducted at Vihara Dharma Ratna, Tangerang, was organized by the Accounting Study Program with the primary objective of enhancing the financial managers’ understanding of financial prioritization. The activity was held on March 16, 2025, and involved lecturers and students as facilitators, with ten participants in attendance. The learning process employed a combination of methods, including lectures, interactive discussions, case study analyses, and practical exercises. The results indicated a significant improvement in participants’ knowledge and skills, particularly in cash flow management, budgeting, and the establishment of structured financial priorities. This program is expected to contribute to the long-term economic well-being of the vihara community through the implementation of systematic and sustainable financial management practices. The success of the activity was reflected in the participants’ enhanced understanding of cash flow management, budgeting, and prioritization concepts, as evidenced by post-test results showing that all participants achieved a perfect score of 100.